2015
DOI: 10.1039/c4sc02789b
|View full text |Cite
|
Sign up to set email alerts
|

Organic/inorganic double-layered shells for multiple cytoprotection of individual living cells

Abstract: S. cerevisiae encapsulated with a poly(norepinephrine)/silica double-layered shell showed multiple resistance to enzymatic attack, desiccation, and UV-C irradiation. The biochemical response of the encapsulated yeast may also contribute to the UV-C resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 34 publications
0
56
0
Order By: Relevance
“…, HeLa cells), in our previous studies1839. After cell encapsulation with the MSi shells, the cell viability was maintained without noticeable decrease, and yeast@MSi retained their basic metabolism and functions, such as cell division, because small molecules, such as O 2 and nutrients, could pass through the MSi shells35. The UV-Visible and SQUID analyses confirmed that the multinary magnetization of yeast cells was achieved by the reactive LbL method that controlled the number of MNPs deposited onto the cell wall.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…, HeLa cells), in our previous studies1839. After cell encapsulation with the MSi shells, the cell viability was maintained without noticeable decrease, and yeast@MSi retained their basic metabolism and functions, such as cell division, because small molecules, such as O 2 and nutrients, could pass through the MSi shells35. The UV-Visible and SQUID analyses confirmed that the multinary magnetization of yeast cells was achieved by the reactive LbL method that controlled the number of MNPs deposited onto the cell wall.…”
Section: Discussionmentioning
confidence: 87%
“…, formation of “cell-in-shell” structures) is to temporarily protect the cells against external stress during manipulation and storage, and to endow the cells with exogenous properties, magnetism in this work31323334. Living cells are generally vulnerable to chemical materials and treatments, and, therefore coating materials and procedures should be cytocompatible35363738394041. In this work, we chose polyamine-stabilized MNPs and silica as coating materials, because these materials proved highly cytocompatible, even in the case of mammalian cells ( e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ESMH was obtained by following our previous report. [33] Yeast@CM was dispersed in an ESMH solution (0.25 mg mL À 1 in the 0.15-M NaCl solution) and gently stirred for 15 min. The ESMH-primed yeast@CM was washed three times with the NaCl solution.…”
Section: Extraction and Characterizations Of High Molecular-weightmentioning
confidence: 99%